Students’ satisfaction and encouragment of learning using google classroom during the Covid-19 pandemic - Sarifa Achmad; Jaka Nugraha (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
Abstrak: Tujuan penelitian ini yaitu untuk menginvestigasi kepuasan dan dorongan belajar menggunakan google classroom di masa pandemi COVID-19 pada institusi. Penelitian ini merupakan penelitian kuantitatif dan metode analisis data yang dipakai yakni Structural Equation Modeling-Partial Least Square (SEM-PLS) melalui aplikasi SmartPLS 3.0. dengan jumlah sampel penelitian sebanyak 130 responden yang terdiri dari mahasiswa yang telah menggunakan platform Google Classroom selama pandemi COVID-19. Hasil menunjukkan variable confirmation dan perceived usefulness secara positif signifikan mempengaruhi variable satisfaction dan continuance intention dalam penggunaan google classroom di masa pandemi COVID-19. Penelitian ini dapat memberikan wawasan baru dalam memelihara literatur keberlanjutan penggunaan teknologi pembelajaran online di masa depan. Abstract: This study attempted to investigate the satisfaction and encouragement of learning using Google classroom during the COVID-19 pandemic in institutions. This research is quantitative research of which data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with the help of the SmartPLS 3.0 application. The 130 respondents consisting of students who have used the Google Classroom platform during the COVID-19 pandemic participated in the study. The results showed that the confirmation and perceived usefulness variables positively and significantly affected the satisfaction and continuance intention variables in the use of Google Classroom during the COVID-19 pandemic. This research can provide new insights into maintaining the literature on the sustainability of the use of online learning technology in the future.